Steroid hormones and influence of therapeutic drugs in Chinese postmenopausal rheumatoid arthritis patients - Zhang, Ying-ying; Yang, Na; Zhang, Hua-yong; Ge, Jia-jia; Yan, Si-min; Han, Dan; Qiu, Qian-ye; Ge, Wei-hong; Shu, Qing (Frontiers in Immunology, 2025)
ObjectiveTo investigate steroid hormone profiles and therapeutic modulation in Chinese postmenopausal rheumatoid arthritis (RA) patients.MethodsThis cross-sectional study enrolled 138 postmenopausal women, including 88 RA patients stratified by treatment status (23 treatment-naïve, 35 on methotrexate [MTX] monotherapy, and 30 receiving MTX plus glucocorticoids [GC]) and 50 age-matched healthy controls. Using liquid chromatography-tandem mass spectrometry (LC-MS/MS), we quantified 36 steroid hormones/metabolites to assess treatment-associated endocrine alterations. Group comparisons employed non-parametric Kruskal-Wallis test for multi-group comparisons, with post-hoc Mann-Whitney U tests and false discovery rate (FDR) correction for multiple comparisons. Statistical significance was defined as p<0.05 after FDR correction.ResultsUntreated RA patients demonstrated significant global steroid dysregulation, characterized by marked suppression of multiple adrenal steroids (including aldosterone, cortisol, and testosterone) compared to healthy controls (all FDR<0.05). This was accompanied by profound alterations in estrogen metabolism, notably a hyperactivated 2-hydroxylation pathway and depleted 16-hydroxylation metabolites (FDR<0.001). MTX treatment partially restored steroid homeostasis, significantly improving aldosterone and androgen profiles (FDR<0.05) toward levels observed in healthy controls. However, the addition of GC therapy further disrupted endocrine balance, significantly suppressing cortisol, testosterone, and total estrogens (FDR<0.05), while pathologically amplifying the 4-hydroxylation pathway (FDR<0.001), a process potentially linked to synovial inflammation.ConclusionsThis study demonstrates that impaired steroidogenesis and estrogen pathway dysregulation are characteristic features of postmenopausal RA, with MTX showing unexpected hormone-restorative effects. While GC therapy provides symptomatic relief, it paradoxically exacerbates endocrine disruption, suggesting the need for personalized hormonal monitoring in long-term GC-treated patients.